2015
DOI: 10.1103/physrevb.91.094106
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen influence on diffusion in nickel from first-principles calculations

Abstract: We propose a method to evaluate the diffusion coefficient of vacancy-hydrogen clusters (VH n ) in metals. The key is a good separation of time scales between H diffusion and the metal-vacancy exchange. The Ni-H system is investigated in details, using ab initio calculations, but the arguments can be transposed to other systems. It is shown that cluster diffusion can be treated as an uncorrelated random walk and that H is always in equilibrium before the vacancy-metal exchange. Then, the diffusion coefficient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The maximal effect is at low T (300 K), where full filled vacancies { VH 6 ) have large concentration for usual H concentra tions. We clearly see that even if VHm should move slowly like in nickel [33], the abundance of vacancies will affects the diffusion of species in aluminum.…”
Section: Statistical Approachmentioning
confidence: 88%
“…The maximal effect is at low T (300 K), where full filled vacancies { VH 6 ) have large concentration for usual H concentra tions. We clearly see that even if VHm should move slowly like in nickel [33], the abundance of vacancies will affects the diffusion of species in aluminum.…”
Section: Statistical Approachmentioning
confidence: 88%
“…It is assumed here that hydrogen charging enhances generation of thermally activated vacancies primarily at grain boundaries and specimen free surfaces. Using the average time for a vacancy diffusion hop in Ni at 600 K (0.6  10 -4 s) [35] the upper value of the characteristic diffusion path for a monovacancy under the applied charging conditions is estimated to be 33 m. This implies the SC and 1-mm grain size samples will Grain size effects on vacancy generation and clustering are assessed as a function of material condition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been seen that a large segregation of H atoms in the vacancies increases significantly the concentration of vacancies, especially at low and intermediate temperatures (below 600 K). It has also been shown that in nickel, hydrogen-vacancy interactions enhance the diffusion mechanisms of solutes or self-interstitial atoms at low temperatures [3].…”
Section: Introductionmentioning
confidence: 99%